Interactive 3D Model Construction From House Plans using Augmented Reality - Gowrisankari, T; Raj, M.Rahul; Kousika, A; Balachandar, G (International Journal of Computer Sciences and Engineering, 2019)
Augmented Reality is an interactive and real-world environment where the objects in the real-world are augmented by computer-generated perceptual information, sometimes across multiple sensory modalities, including visual, auditory, haptic, and somatosensor. Augmented Reality (AR) is a new interface technology which brings 3D model in the real time environment. To manipulate 3D models in real time environment through the Smartphone's Vuforia technology is used. Visualization of the model can be done by using HMD (Head Mounted Display). Develop a model which will forecast a dynamic 3D model from 2D house plans. The system assembles 3D models and overlays virtual model on the real 2D Blueprint of the house (Architectural/Hand-drawn). Harris corner detection algorithm is used and Detection of Doors/Windows are done through Template matching algorithm. It is mainly based on Image Processing by using OpenCV library functions.